An Examination of Primary School Teachers’ Views on the Use of New Letter Groupings in Initial Literacy Instruction under the Century of Türkiye Education Model - Zengin, Erdal; Duyu, Ebuzer (Marmara Üniversitesi, 2026)
The aim of this study is to examine the effects of the newly implemented letter groupings, introduced within the scope of the “Century of Türkiye Education Model,” on initial literacy instruction based on the opinions of primary school teachers. A case study design was adopted, and the participant group was determined through maximum variation sampling. In this context, 50 teachers from urban, district, and village schools across five different cities participated in the study. The interview method was employed as the data collection technique, with interviews conducted both face-to-face and online depending on participants’ availability. A semi-structured interview form, developed by the researchers, served as the data collection instrument. The data obtained from the interviews were transcribed and subjected to content analysis using the MAXQDA software. During the data analysis process, the data were coded independently by the authors, and the consistency of the generated codes was evaluated. Based on the findings, it was emphasized that the contents of the new initial literacy textbook were evaluated positively by primary school teachers, although certain shortcomings were also noted. In comparing literacy instruction with the new and the former letter groupings, it was concluded that literacy instruction with the former letter groupings was easier, more functional, and more advantageous compared to the new ones. However, literacy instruction with the new letter groupings was reported to enhance students’ motivation, and the simplification introduced in the program—reflected in the new initial literacy textbooks—was considered a positive development.

Bu çalışmanın amacı, ‘Türkiye Yüzyılı Maarif Modeli’ kapsamında uygulamaya konan yeni harf gruplarının ilk okuma-yazma öğretimine etkilerini sınıf öğretmenlerinin görüşleri doğrultusunda incelemektir. Çalışmanın deseni olarak durum çalışması deseni tercih edilmiş ve çalışmanın katılımcı grubu maksimum çeşitlilik örnekleme yöntemiyle belirlenmiştir. Bu kapsamda il, ilçe ve köy okullarından olmak üzere 5 farklı şehirden 50 öğretmen çalışmaya dâhil edilmiştir. Çalışmada veri toplama yöntemi olarak görüşme yöntemi kullanılmıştır. Katılımcıların uygunluk durumlarına göre yüzyüze ve çevrim içi görüşmeler gerçekleştirilmiştir. Veri toplama aracı olarak, araştırmacılar tarafından hazırlanan yarı yapılandırılmış görüşme formu kullanılmıştır. Görüşmelerden elde edilen veriler yazılı hale getirilmiş ve MAXQDA programı ile içerik analizine tabi tutulmuştur. Veri analizi sürecinde, veriler yazarlar tarafından ayrı ayrı kodlanarak elde edilen kodların uyumları değerlendirilmiştir. Çalışmanın bulgularından hareketle elde edilen sonuçlar doğrultusunda yeni ilk okuma yazma kitabına dair içeriklerin sınıf öğretmenleri tarafından olumlu olarak değerlendirildiği ancak yine de bazı eksikliklerinin olduğu vurgulanmıştır. Yeni ve eski harf gruplarıyla okuma yazma öğretiminin karşılaştırılmasında; eski harf gruplarıyla okuma yazma öğretiminin yeni harf gruplarıyla okuma yazma öğretimine göre daha kolay, işlevsel ve avantajlı olduğu sonucuna ulaşılmıştır. Yeni harf gruplarıyla okuma yazma öğretiminin ise öğrencilerde motivasyonu artırdığı ifade edilmiş ve programda yapılan dolayısıyla ilk okuma yazma ders kitaplarına da yansıyan sadeleştirmenin olumlu olarak değerlendirildiği belirlenmiştir.
Sınıf Öğretmenlerinin Türkiye Yüzyılı Maarif Modeli’ne Göre İlkokuma Yazma Öğretiminde Yeni Harf Gruplarının Kullanılmasına İlişkin Görüşlerinin İncelenmesi
Keywords: Curriculum Evaluation in Education; Eğitimde Program Değerlendirme; Specialist Studies in Education (Other); Eğitim Üzerine Çalışmalar (Diğer)